Insights from serial cardiovascular magnetic resonance imaging show early progress in diastolic dysfunction relates to impaired right ventricular deformation - Sören J. Backhaus; Alexander Schulz; Torben Lange; Simon F. Rösel; Lennart S. Schmidt-Schweda; Shelby Kutty; Johannes T. Kowallick; Julia Treiber; Andreas Rolf; Samuel Sossalla; Gerd Hasenuß; Andreas Schuster (Scientific Reports)
Abstract Latent pulmonary vascular disease is a distinct feature already in the early pathophysiology of masked heart failure with preserved ejection fraction (HFpEF) and associated with reduced right ventricular (RV) functional reserve. We hypothesized that serial real-time cardiovascular magnetic resonance (CMR) imaging at rest and during exercise-stress may detect early progress in pathophysiological alterations in HFpEF. Patients presenting with exertional dyspnoea and signs of diastolic dysfunction (E/e’>8, left ventricular (LV) ejection fraction > 50%) were prospectively enrolled in the HFpEF Stress Trial (NCT03260621). Rest and exercise-stress echocardiography, CMR and right heart catheterisation were performed at baseline. Pulmonary capillary wedge pressure (PCWP) was used for classification of HFpEF (≥ 15/25mmHg at rest/during exercise-stress) and non-cardiac dyspnoea (NCD). Repeat rest and exercise-stress CMR was performed in median 2.94 years after recruitment during which timeframe some HFpEF patients had undergone interatrial shunt device (IASD) implantation. Cardiovascular events were assessed after 4 years.Serial CMR scans were available for NCD n = 10, HFpEF n = 10 and HFpEF with IASD implantation following baseline diagnosis n = 6. RV long axis strain at rest and during exercise-stress decreased in HFpEF (p = 0.007 for both) but neither in NCD nor HFpEF with IASD. In contrast, in NCD, an improvement in LA LAS during exercise-stress (p = 0.028) was noted. There were no functional alterations in HFpEF patients who had undergone IASD implantation. RV functional deterioration may be a pathophysiological feature during early-stage disease progress in HFpEF. In this observational study RV functional deterioration was detected in HFpEF patients only but not patients with NCD and patients with HFpEF that were treated with IASD placement. These findings should next be explored in adequately powered future research trials. Clinicaltrials.gov: NCT03260621 (First posted date 24/08/2017).